Psychological characteristics and entrepreneurial intention: a study among university students in north Borneo, Malaysia - Sorayah Nasip; Sharifah Rahama Amirul; Stephen Laison Sondoh Jr.; Geoffrey Harvey Tanakinjal (Emerald Group Publishing Ltd., 2017)
Purpose: The aim of this study is to investigate the relationship between individuals’ psychological characteristics (i.e. innovativeness, locus of control, self-confidence, propensity to take risk, need for achievement, and tolerance for ambiguity) and entrepreneurial intention. Design/methodology/approach: A total of 676 undergraduate students from Universiti Malaysia Sabah (UMS) participated in the survey. Data was analyzed using Partial Least Square (PLS) technique version 2.0. Findings: The results show that innovativeness, self-confidence, propensity to take risk, need for achievement and tolerance for ambiguity are positively related to entrepreneurial intention among undergraduate students. However, locus of control was found not significantly related to entrepreneurial intention. Research limitations/implications: Although, samples of our study are quite large, but this study only involves undergraduate students in UMS. Therefore, findings obtained are not generalized because the results do not include other educational institutions in Malaysia. On the implication aspect, this study might give some views among undergraduate students to embark in business after graduating. Practical implications: In spite of that, students should be encouraged and equip with innovativeness, self-confidence, propensity to take risk, need for achievement and tolerance for ambiguity to interpret successful entrepreneurial role models and identification of business prospects for their future career. Originality/value: The findings of the study may extend existing knowledge in the entrepreneurial field as well as to provide valuable information to policy maker in strengthens and redesigning suitable curriculum not only in university level but also in pre-school by giving entrepreneurial awareness on how this knowledge will transforming us into an entrepreneurial society that can create wonder for human kind.